Portrait of Debt Accounting Based on Feeling and Faith: a Study of Islamic Ethnomethodology - Mohamad Anwar Thalib (Maqrizi: Journal of Economics and Islamic Economics, 2022)
This study aims to construct debt accounting based on feelings and faith. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and good deeds. The study's results found that the source of household debt came from parents and lending institutions. Debt obtained through parents is more flexible regarding time and nominal repayment. This is different from debt obtained from lending institutions. The informants carried out the method of recording debt accounting both in memory and on paper. The practice of debt accounting is conditioned by the feeling of being uneasy, unpleasant, and depressed, even the fear that God will take a life while still in debt. The findings from this study reinforce that, in essence debt accounting is not limited to material (money) but conditions with a sense of and faith in the Creator